25 Years of Operation of the ‟Santa María De Loreto” Photovoltaic Plant, Cuba - José Emilio Camejo Cuán; Rubén Ramos Heredia; Roger Proenza Yero; José Felipe Vigil (Journal La Multiapp, 2022)
The work addresses the main socio-technological aspects of the electrification process with photovoltaic solar technology , during 25 years of exploitation, in the rural community "Santa María del Loreto" and its necessary relationship with its beneficiaries, where participation, training and the use of resource rules such as those main variables that favor the assimilation of this technology, modifying habits and customs of the users in terms of energy consumption in a collectivist manner, which have allowed the promotion of endogenous capacities for the community appropriation of photovoltaic technology in substitution of a Diesel Generators, as an electrification route.